PENGARUH PENGETAHUAN HYGIENE DAN SANITASI TERHADAP PENYELENGGARAAN MAKANAN SEHAT PADA KELOMPOK KERJA GURU (KKG) SD KECAMATAN KELING JEPARA JAWA TENGAH - Salis Milla Rohma (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2016)
This paper aimed to know (1) hygieneand sanitation knowledge, (2) family healthfood service, and (3) the influence of hygieneand sanitation knowledge toward familyhealth food service among the elementaryschool teachers of teacher working groupsKeling District Jepara. The type of this paperwas ex-post facto. Data collection techniquesused questionnaire and documentation. Dataanalysis technique used descriptive analysisand hypothesis testing by using Product Moment correlation that was started by normality and linearity test. This paper shows thathygiene and sanitation knowledge was inenough category with the percentage 48.62%and family health food service was in enoughcategory with the percentage 63.89%. Basedon the analysis, the score of rxy was 0.408.The score of r table in the significant level 5%for total respondents 75 was 0.235 (rxy0,408> r table 0,235). It means that there wasa positive and significant influence of hygiene and sanitation knowledge toward family health food service among the elementaryschool teachers of teacher working groupsKeling District Jepara. The score of determinant coefficient (R2) was 0.166, it means thathygiene and sanitation knowledge gave apositive contribution 16.6% toward familyhealth food service, while 83.4% was influenced by other factors that were not analyzedin this paper.